2017
DOI: 10.1155/2017/2186383
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Endocannabinoid Receptor 2 as a Mechanism of Propofol Pretreatment‐Induced Cardioprotection against Ischemia‐Reperfusion Injury in Rats

Abstract: Propofol pretreatment before reperfusion, or propofol conditioning, has been shown to be cardioprotective, while its mechanism is unclear. The current study investigated the roles of endocannabinoid signaling in propofol cardioprotection in an in vivo model of myocardial ischemia/reperfusion (I/R) injury and in in vitro primary cardiomyocyte hypoxia/reoxygenation (H/R) injury. The results showed that propofol conditioning increased both serum and cell culture media concentrations of endocannabinoids including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
(71 reference statements)
2
27
0
Order By: Relevance
“…In support of these findings, the cytoprotective effect of propofol is abolished by CB2 antagonists, although not by CB1 antagonists [118]. An effect similar to propofol is exhibited by an FAAH inhibitor (URB597) and an endocannabinoid reuptake inhibitor (VDM11) [118]. In addition, the exposure of neurons to another endocannabinoid-oleoylethanolamine (OEA)-also exerts a neuroprotective effect, in a manner dependent on the PPARα receptors of hypoxic neurons, which would otherwise cause their apoptosis, in part by increasing Bax expression and decreasing Bcl-2 levels [119,120].…”
Section: Endocannabinoidssupporting
confidence: 54%
See 1 more Smart Citation
“…In support of these findings, the cytoprotective effect of propofol is abolished by CB2 antagonists, although not by CB1 antagonists [118]. An effect similar to propofol is exhibited by an FAAH inhibitor (URB597) and an endocannabinoid reuptake inhibitor (VDM11) [118]. In addition, the exposure of neurons to another endocannabinoid-oleoylethanolamine (OEA)-also exerts a neuroprotective effect, in a manner dependent on the PPARα receptors of hypoxic neurons, which would otherwise cause their apoptosis, in part by increasing Bax expression and decreasing Bcl-2 levels [119,120].…”
Section: Endocannabinoidssupporting
confidence: 54%
“…This is accompanied by increased activation of CB1 and CB2 receptors at both mRNA and protein levels. In support of these findings, the cytoprotective effect of propofol is abolished by CB2 antagonists, although not by CB1 antagonists [118]. An effect similar to propofol is exhibited by an FAAH inhibitor (URB597) and an endocannabinoid reuptake inhibitor (VDM11) [118].…”
Section: Endocannabinoidsmentioning
confidence: 77%
“…CB 2 receptor expression in non-pregnant females has been demonstrated to be cardioprotective, with up-regulation decreasing risk of cardiovascular diseases. 29 In further support of a beneficial role for CB 2 , the activation of the receptor increases the production of anti-inflammatory proteins. 30 Although we have not investigated cardiovascular function in mothers consuming elevated LA diets and circulating concentrations of proinflammatory cytokines appear unaltered, 3 the current data suggest that elevated LA during pregnancy may modify maternal cardiovascular function.…”
Section: Discussionmentioning
confidence: 97%
“…The involvement of CB2 in I/R injury has also been investigated in a context of propofol cardioprotection in an in vivo model of myocardial I/R injury, in which it has been observed that CB2 inactivation reverses propofol cardioprotective and anti-oxidative effects [ 230 ]. These findings imply that the enhancement of ECs release and the subsequent activation of CB2 signaling are responsible for the reduced oxidative stress mediated by propofol cardioprotection in myocardial I/R injury [ 230 ].…”
Section: Modulation Of Oxidative Stress and Lipid Peroxidation Thrmentioning
confidence: 99%